Rekayasa Budaya dan Dinamika Sosial: Menemukan Pokok Pikiran Lokalitas Budaya Sebagai Daya Cipta - Erond Litno Damanik (Mahesa Research Center, 2018)
This paper discusses cultural engineering on social dynamics, namely culture as the creativity of facing social change. In this paper, social dynamics is a creative response from the culture support community that originates from ideas which are then channeled into activities and appear in human artifacts. Social dynamics are not always supported by formal institutions but are also supported by informal institutions, namely cultures that play an active role. The idea that the origin of activities and artifacts in culture is a way of thinking that is a creative response to creativity. As for the problem in this study, is it true that culture can be engineered into creativity? The results of the study show that culture can be engineered as a creative power as an agent of social dynamics by: (i) recording and filtering out the thoughts of cultural locality, (ii) formulating and designing strategies for developing locality culture, (iii) building cultural locality pranata , (iv) disseminating and instilling the core of cultural locality, (v) making regulations protect the core thoughts of cultural locality, and (vi) applying basic things to cultural locality as agents of social dynamics.